Dimensionen der Erziehung und Bildung - Hoffmann-Ocon, Andreas; Koch, Katja; Schmidtke, Adrian (Universitätsverlag Göttingen, 2005)
Central historical, biographical and school-related aspects of formation and education are brought together in this work to point to the diversity of educational sciences. Tradition and innovation are recurrent themes in all the articles. As Friedrich Schleiermacher puts it in his understanding of generations as constituent aspect of pedagogy itself: only who fathoms the tradition and who is aware of the tradition will be able to be innovative - and only an innovative person is able to recognize tradition.Central historical, biographical and school-related aspects of formation and education are brought together in this work to point to the diversity of educational sciences. Tradition and innovation are recurrent themes in all the articles. As Friedrich Schleiermacher puts it in his understanding of generations as constituent aspect of pedagogy itself: only who fathoms the tradition and who is aware of the tradition will be able to be innovative - and only an innovative person is able to recognize tradition.